Hadith Study on Human “Fitrah” in The Hadith Literacy and Its Implication in The Islamic Education System: Kajian Hadis tentang “Fitrah” Manusia dalam Literasi Hadis dan Implikasinya dalam Sistem Pendidikan Islam - Mada Wijaya Kusumah; Hidayat, Tatang; Elan Sumarna; Istianah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The inability of the modern education system to respond to various social problems raises new issues regarding the effectiveness of the education system. The rise of educational system approaches that refer to Western traditions, such as the concept of “tabula rasa” initiated by John Locke, actually exacerbates the existing problems, because there is a dichotomy between knowledge science and religion. Thus, education is no longer able to direct each student to the moral values that have been taught by the predecessors. Departing from the dynamics that occur, this research aims to examine the hadith about fitrah as a new formulation in the Islamic education system. Two questions become the initial basis of the study: first, how is human nature in the literacy of the Prophet's hadith; second, what are the implications of the concept of fitrah in the formulation of Islamic education? Through literature-based qualitative methods, the results show that the hadith about fitrah is massively spread with ittishal. The concept of fitrah in the hadith indicates that every human being is born with a natural tendency towards monotheism and stands on good values. In the framework of Islamic education, this concept becomes the epistemological basis that the educational process is a process of maintaining and actualizing fitrah, so that education is not just a transfer of knowledge, but rather forming an integral personality that is in line with divine values. Thus, the implementation of Islamic education needs to emphasize approaches that recognize the sacred potential in children and design curriculum and learning methods that support the development of fitrah holistically.